The challenges of telemedicine in the Czech Republic from an expert perspective - Těšinová, Jolana Kopsa; Dobiášová, Karolína (Casopis lekaru ceskych, 2022)
Health policy makers are striving to implement new approaches in healthcare with a focus on digital solutions. The COVID-19 pandemic has contributed to an unprecedented acceleration in the spread of information and communication technologies (ICT) in healthcare and has accelerated the use of telemedicine. The aim of the research was to identify problems related to the implementation of telemedicine in practice, to propose possible solutions and to identify the challenges of telemedicine in the Czech Republic in the future. The study is based on the results of a two-phase qualitative expert investigation. Data collection in the first phase took the form of individual semi-structured interviews with experts who have practical experience in the field of telemedicine. The follow-up second phase was conducted in the form of guided group discussions with experts focusing on health, financial and legislative aspects of telecare. It turned out that the introduction and expansion of telemedicine requires changes in the technological infrastructure, in the organization of care and work, and in the adjustment of the legislative environment. It is also necessary to consider the need to overcome several barriers at the level of the healthcare system, healthcare providers, healthcare professionals and patients. On the other hand, a condition for the successful introduction and development of telemedicine is coordinated cooperation between various institutions and stakeholders. The introduction of telemedicine should also be preceded by studies (research) and in-depth analyses. Telemedicine education of healthcare professionals and support for patients in developing their digital competences are also important.
Keywords: Telemedicine; health care organization; pandemie; COVID-19; telemedicína; Pandemics; data sharing; digitization of health care; Humans; telemedicine; Česká republika; lidé; information and communication technologies; Delivery of Health Care; digital literacy; poskytování zdravotní péče; Czech Republic